PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SQUARE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK FASE E SMA NEGERI 5 PADANG - Yuza, Dhiya Aqilah (Departemen Matematika, 2023)
If we talks about learning of mathematics, one of the goals is in order that the students are able to get communication of mathematics ability, however the students at Phase E SMA Negeri 5 Padang have not been successful in doing so. The results of this ability's initial testing account for this. The TPSQ (Think Pair Square) cooperative learning model, which focuses on equation and square function resources, is used to effort this issue by enhancing the students' mathematical communication abilities. The Phase E SMA Negeri 5 Padang student population for the academic year 2022-2023 is used in this research. Quasy experiment and Nonequivalent Posttest-Only Control Group Design were used in this study. Two groups of samples are collected using simple random sampling. Quizzes and final test of mathematical ability are the study's instruments. The test-t is employed to demonstrate the research hypothesis. 0,004 is the P-value, based on data analysis. When the P-value is < α=0,05, is either rejected or accepted . In summary, at SMA Negeri 5 Padang's Phase E, students who use the TPSQ cooperative learning model have superior mathematics communication abilities than those who use the direct learning approach.Keywords– Cooperative Learning Model Type Think Pair Square, Mathematical Communication Abilities